Chalepogenus roitmani Roig Alsina (Hymenoptera: Apidae: Tapinotaspidini): description of the male and new geographical records for the species - Torretta, Juan Pablo; Marrero, Hugo J.; Alsina, Arturo Roig (Zootaxa, 2011)
Bees of the genus Chalepogenus Holmberg collect oils offered as a reward by flowers of a few plant families: Iridaceae, Calceolariaceae (formerly included in Scrophulariaceae, see Olmstead et al. 2001), and Solanaceae (Vogel 1974; Cocucci 1991; Roig Alsina 1999; Cocucci et al. 2000; Machado 2004). The oil-collecting structures of these bees are situated on the forebasitarsus and show interspecific variation related to the type of flower they visit (Roig Alsina 1997; Cocucci et al. 2000).